Membumikan Ilmu Sosial Profetik: Reaktualisasi Gagasan Profetik Kuntowijoyo dalam Tradisi Keilmuwan di Indonesia - Putri Wulansari, Nurul Khotimah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2019)
Abstract Not only does modernization offer technological sophistication and convenience for all human activities, but this phenomenon also presents a phase called the post-truth era. This phenomenon occurs when the loss of the existence of scientists or intelligentsia by the anti-intellectualism movement which is called the death of expertise. The term death of expertise which was popularized by Tom Nichols eventually became so popular globally including in Indonesia. At least the post-truth era, the death of expertise and the industrial revolution 4.0 became a very popular issue in Indonesia, so that it indirectly showed stuttering and acute inferiority in the scientific tradition in Indonesia. Because in the 90s the Indonesian Muslim scholar Kuntowijoyo had dismissed the phenomena and problems of modern society through his collection of essays such as Muslims without Mosques and Political Identity of Muslims. Therefore this paper uses a descriptive qualitative approach aimed at describing the urgency of the re-actualization and revitalization of prophetic social science in the perspective of Kuntowijoyo's thoughts. In addition, the Prophetic Social Sciences (ISP) is also placed in the Indonesian context so that Indonesia is able to have an authentic scientific tradition, and be able to deliver the Indonesian people to face all the challenges of changing times without losing the humanity and rationality. Furthermore, this paper also presents the problem of the development of science in Indonesia to highlight the urgency of the reactualization of prophetic Social Sciences in the scientific tradition in Indonesia. Keywords: Reactualization, Prophetic Social Sciences and Kuntowijyo. Abstrak Modernisasi tidak hanya menawarkan kecanggihan teknologi serta kemudahan bagi segala aktivitas manusia, tetapi fenomena ini turut menghadirkan sebuah fase yang disebut sebagai era pasca kebenaran. Fenomena ini terjadi ketika hilangnya eksistensi ilmuwan atau kaum intelegensia oleh gerakan anti intelektualisme yang disebut sebagai matinya kepakaran. Istilah matinya kepakaran yang dipopulerkan oleh Tom Nichols tersebut akhirnya menjadi begitu populer secara global termasuk di Indonesia. Setidaknya era pasca kebenaran, matinya kepakaran dan revolusi industri 4.0 menjadi isu yang sangat digemari di Indonesia, sehingga secara tidak langsung memperlihatkan kegagapan dan inferioritas akut dalam tradisi keilmuwan di Indonesia. Sebab di era 90-an cendikiawan Muslim Indonesia Kuntowijoyo telah menganggas fenomena dan problematika masyarakat modern melalui kumpulan esai-esainya seperti Muslim tanpa Masjid dan Indentitas Politik Umat Islam. Oleh karenanya tulisan ini menggunakan pendekatan kualitatif deskriptif bertujuan memaparkan mengenai urgensi dari reaktualisasi dan revitalisasi ilmu sosial profetik dalam persfektif pemikiran Kuntowijoyo. Selain itu, Ilmu Sosial Profetik (ISP) ini turut diletakkan dalam konteks keindonesia sehingga Indonesia mampu memiliki tradisi keilmuwan yang autentik, serta mampu mengantarkan bangsa Indonesia menghadapi segala tantangan perubahan zaman tanpa kehilangan sisi humanitas dan rasionalitas. Selanjutnya, dalam tulisan ini turut dihadirkan problematika pengembangan ilmu pengetahuan di Indonesia untuk menegaskan urgensi dari reaktualisasi Ilmu Sosial profetik dalam tradisi keilmuwan di Indonesia. Kata kunci: Reaktualisasi, Ilmu Sosial Profetik dan Kuntowijyo.